Liposomal doxorubicin attenuates cardiotoxicity via induction of interferon-related DNA damage resistance. Issue 5 (25th July 2019) - Gyöngyösi, Mariann; Lukovic, Dominika; Zlabinger, Katrin; Spannbauer, Andreas; Gugerell, Alfred; Pavo, Noemi; Traxler, Denise; Pils, Dietmar; Maurer, Gerald; Jakab, Andras; Riesenhuber, Martin; Pircher, Andreas; et al.
Abstract: Aims: The clinical application of doxorubicin (DOX) is severely compromised by its cardiotoxic effects, which limit the therapeutic index and the cumulative dose. Liposomal encapsulation of DOX (Myocet ® ) provides a certain protective effect against cardiotoxicity by reducing myocardial drug accumulation. We aimed to evaluate transcriptomic responses to anthracyclines with different cardiotoxicity profiles in a translational large animal model for identifying potential alleviation strategies. Methods and results: We treated domestic pigs with either DOX, epirubicin (EPI), or liposomal DOX and compared the cardiac, laboratory, and haemodynamic effects with saline-treated animals. Cardiotoxicity was encountered in all groups, reflected by an increase of plasma markers N-terminal pro-brain-natriuretic peptide and Troponin I and an impact on body weight. High morbidity of EPI-treated animals impeded further evaluation. Cardiac magnetic resonance imaging with gadolinium late enhancement and transthoracic echocardiography showed stronger reduction of the left and right ventricular systolic function and stronger myocardial fibrosis in DOX-treated animals than in those treated with the liposomal formulation. Gene expression profiles of the left and right ventricles were analysed by RNA-sequencing and validated by qPCR. Interferon-stimulated genes (ISGs), linked to DNA damage repair and cell survival, were downregulated by DOX, but upregulated by liposomal DOX in both the left and right ventricle. The expression of cardioprotective translocator protein (TSPO) was inhibited by DOX, but not its liposomal formulation. Cardiac fibrosis with activation of collagen was found in all treatment groups. Conclusions: All anthracycline-derivatives resulted in transcriptional activation of collagen synthesis and processing. Liposomal packaging of DOX-induced ISGs in association with lower cardiotoxicity, which is of high clinical importance in anticancer treatment. Our study identified potential mechanisms for rational development of strategies to mitigate anthracycline-induced cardiomyopathy. Graphical Abstract: